Manifestações cardiovasculares relacionadas à infecção por Sars-cov-2: uma revisão atualizada - Santos, Flávio Campagnoli dos (2023)
Introduction: COVID-19 is a disease caused by the SARS-CoV-2 virus, discovered in China in December 2019. It quickly established itself as a pandemic, causing multiples cases of Severe Acute Respiratory Syndrome around the world. However, typical alterations of the cardiovascular system were also observed, such as: myocardial injury, myocarditis, acute myocardial infarction, heart failure, dysrhythmias and thromboembolic events. Objective: To describe the main cardiac manifestations related to COVID-19. Methods: This research is a systematic review of the literature. The bibliographic survey was carried out in November 2022 in the PubMed, Scielo and BVS databases. The initial search totaled 3,770 articles and, after applying filters, eliminating duplicates and applying the eligibility criteria, 20 articles were used in the review. In addition to those selected, 23 articles were added. Results: 20 articles were found relating COVID-19 with the following cardiovascular manifestations: Myocardial injury, acute myocardial infarction, heart failure, arrhythmias and perimyocarditis. These cardiovascular manifestations may have their genesis through the direct cardiotropism of the virus, or through the cytokine storm, an immunological manifestation with multisystem involvement. Myocardial injury usually precedes the other manifestations, with a significant average incidence (27.8-54%), and all have evidence of a worse prognosis in the course of COVID-19, with increased hospital mortality. Conclusion: Therefore, further investigation of cardiovascular outcomes in patients hospitalized for COVID-19 is necessary, as they have a high incidence and are directly related to increased mortality. Screening using myocardial injury markers, such as cardiac troponins, has increasingly demonstrated its prognostic value in this context.